Baraka, performative healing and the Moroccan Sufi chant. (1st January 2013) - Waugh, Earle
A prominent theme in studies of Islamic religio-philosophical systems has been the supposed uptake of key Greek traditions on health and the body. Even those concerned with mysticism have reflected certain ideological interests: most studies of Sufi tradition focus upon either the distinctive mystical doctrines of the group or the trance produced in their rites or the interaction of text and musical formations. This article approaches the tradition from a different perspective. It focuses its attention on key elements in Sufism, but not on either the ideological or textual dimensions. It looks to the performative aspects of dhikr and the chanters who are integrated into it, and especially to note the way in which baraka provides an underlying rationale for health/well-being for all participants (including onlookers). Further, since the dhikr goals are clearly central for all Sufis (i.e. spiritual encounters), the role of the body, body postures and ritual movements all argue for approaching and critically analysing both them and baraka for their larger delivery of meaning. All this suggests a much different mind–body relationship than encountered in the Greek tradition. Examples will be drawn from fieldwork among Morocco's Sufi chanters.